Pengaruh penggunaan air pendingin kondensor terhadap hasil destilasi sampah plastik kapasitas 3 kg - Nur Aini Uwar; Erol Richard Soselissa (Universitas Muhammadiyah Metro, 2022)
In general, plastics have low density, are insulating to electricity, have varying mechanical strength, limited temperature resistance, and varying chemical resistance so that they are widely used because of their advantages. Efforts to manage plastic waste practically and effectively to reduce the widespread pollution. The purpose of this study was to find out the effect of the use of condenser cooling water on the results of the distillation of plastic waste capacity of 3 Kg. Testing was carried out in two ways: measuring the relationship of the time and heat of the kettle, the relationship of time and heat of the condenser. The results showed that the longer time achieved will be the greater the increase in the temperature of the kettle obtained that is 650C to 720C means a change (720C - 650C = 70C), and the longer time achieved will be less heat obtained ie heat value of 2805.688125 and hour later decreased by 2622.88125. In conclusion, the longer the time reached at the time of energy administration in the kettle and the provision of energy to the condenser, the greater the increase in the temperature of the kettle.